Payout characteristics of anabolic agents from Synovex®, Finaplix®, and Revalor® implants in finishing yearling steers - P.S. Hickman; Robert T. Brandt Jr.; D.M. Henricks; J. Ernest Minton; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1994)
Forty, individually fed, yearling steers (750 lbs) were used to measure payout characteristics of different trenbolone acetate-containing implants and to correlate those characteristics to growth response. Treatments were 1) control, 2) Synovex-S®, 3) Finaplix-S®, 4) Synovex® plus Finaplix, and 5) Revalor®. Steers were fed a 12% crude protein, corn-based, finishing diet for 112 days. Compared to Revalor, which had a fairly constant payout over time, the combination of Synovex plus Finaplix resulted in higher blood levels of estradiol and trenbolone acetate (TBA) up to 56 days, followed by a relatively rapid decline to 112 days. Despite elevated levels of TBA at 112 days for all TBA-containing implants and elevated estradiol at 112 days from Revalor steers, implants did not improve performance in the final 28 days before slaughter. Short (less than 120 days) feeding periods may favor implants that increase blood levels of anabolics for shorter (56-84 day) periods. Data for plasma urea nitrogen were interpreted to indicate that 12% crude protein was adequate for yearling steers gaining approximately 3.5 lbs per day.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Trenbolone acetate; Estradiol; Serum hormones; Feedlot